Intention to Use PayLater among Young Muslim Consumers: The Role of Islamic Religious Commitment - Sulhaini Sulhaini; Baiq Handayani Rinuastuti; Siti Nurmayanti (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: Compared to other consumer groups, young Indonesian consumers have a stronger desire for debt and overconsumption Purpose: This study aims to develop and empirically test a model of the influence of materialism and global luxury brand admiration on conspicuous consumption and intention to use conventional PayLater, with Islamic religious commitment as a moderating variable. Method: Data was collected from consumers on the island of Lombok, Indonesia. The island was chosen because it is widely known for its religious community. The study followed a quantitative approach. The respondents were young Muslim consumers between 17 and 35 years of age who were active shoppers in the marketplace. This research involved 364 conveniently selected respondents. Findings: The study indicates that Islamic religious commitment can mitigate the influence of materialism on conspicuous consumption. This commitment also reduces the impact of conspicuous consumption on the willingness to go into debt by using conventional PayLater. The findings also reveal that young Muslim consumers desire global luxury brands to show off. Conclusions: Islamic religious commitment weakens materialism's influence on conspicuous consumption and intention to use PayLater because consumers understand and obey their religion's teachings. Youthful materialistic Muslim consumers may seek comfort, equilibrium, and a high quality of life rather than a desire to flaunt their possessions. Research implication: This study indicates that young Muslim consumers could become the largest users later. To assist them in avoiding riba, PayLater’s owners should provide services according to Islamic teaching and/or encourage them to restrict their use of its services to less than the interest-free period of 30 days.